Revitalisasi Pangan Tradisional : Uji Potensi Daun Kesi (Lannea coromandelica) dalam Fermentasi Uwi Kaju Lamu - Veronika P. Sinta Mbia Wae; Melania Priska; Ainun Jariyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Fermentation is an important process in the processing of traditional food of the Lio tribe, one of which is uwi kaju lamu. This study aims to examine the potential of kesi leaves (Lannea coromandelica) as a natural fermentation agent in the traditional food uwi kaju lamu, a typical food of the Lio Tribe in Ende Regency, East Nusa Tenggara. The research method used is a mix method with a sequential exploratory design (qualitative and quantitative). The qualitative method (interviews, observations, and FGD) aims to confirm the traditional knowledge of the community regarding the use of kesi leaves in the fermentation process of uwi kaju lamu, while the quantitative method is tested in the laboratory. The results showed that the cyanide level of 6 mg/kg was far below the maximum threshold of 50 mg/kg, making it safe for consumption. Secondary metabolite compounds were detected only saponins, while other compounds were not detected indicating degradation of complex components. A pH value of 9.18 (alkaline) indicates contamination in the traditional fermentation process, so further research is needed. Organoleptic tests on 30 untrained panelists showed that the taste aspect showed a high acceptance rate (of 7.47) from an average preference above 7.00 on a scale of 5-9. Overall, kesi leaves have the potential as a natural fermentation agent in the processing of uwi kaju lamu.